Knowledge and attitude of consumer towards adoption of biodegradable food packaging in Kelantan - Noorhamizah Kamaruddin (2022)
Biodegradable packaging is made from few materials as well as the source of materials used is reliable and safe along its life cycle and most importantly the materials can be used and recycled. Since biodegradable materials are very helpful to save the environment from plastic pollution, then biodegradability is applied to food packaging. However, consumer awareness of this must be increased in order to succeed in the mission of saving the world from plastic pollution. Thus, this study was conducted to measure the level of awareness of consumers towards adoption of biodegradable food packaging in Kelantan. In addition, this study is also to identify the knowledge, attitude and practice of consumers towards biodegradable food packaging. This study was conducted to achieve three objectives which were the first objective was to determine knowledge level of consumer on adoption of biodegradable food packaging. Next objective was to identify the relationship between of demographic factor and attitude of consumer towards biodegradable food packaging and to study the most significance factor influencing consumer awareness towards biodegradable food packaging. Conceptual framework for this study was KAP (knowledge, attitude and practice) model. The method for the study was a questionnaire survey which was distributed in online form. The survey was responded by 200 consumers living in Kota Bharu, Kelantan. Results from data analyzed using Statistical Package for Social Science (SPSS) software indicated that knowledge level of consumer towards adoption of biodegradable food packaging was high. Then, demographic factor that have a relationship with attitude of consumer towards adoption of biodegradable food packaging were only educational level, residence area and occupation. Knowledge was the most significance factor influencing consumer awareness towards adoption of biodegradable food packaging in Kelantan. It can be concluded most consumers in Kota Bharu know about biodegradable food packaging and also affect their awareness of on biodegradable food packaging.